2015
DOI: 10.18357/ijih92201214358
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Elders’ and Seniors’ Perceptions of How Climate Change is Impacting Health and Well-being in Rigolet, Nunatsiavut / ᕿᒥᕐᕈᓂᖅ ᐃᓐᓇᐃᑦ ᐊᒻᒪᓗ ᐃᓄᑐᖃᐃᑦ ᐃᓱᒪᔾᔪᓯᖏᓐᓂᒃ ᕆᒍᓚᑦ, ᓄᓇᑦᓯᐊᕗᒻᒥ ᓯᓚᐅᑉ ᐊᓯᔾᔨᐸᓪᓕᐊᓂᖓᓂᒃ ᐊᑦᑐᐃᓂᖃᖅᑎᓪᓗᒍ ᐃᓗᓯᕐᒥᒃ ᐊᒻᒪᓗ ᖃᓄᐃᓐᖏᓂᖏᓐᓂᒃ

Abstract: Climate changes are rapidly intensifying and can lead to adverse global health impacts. Indigenous populations are especially vulnerable to climate change because of their dependence on the environment for cultural activities and subsistence. The voices of Inuit Elders and seniors encompass deep wisdom and history; as such, the goal of this research was to examine the perceived impacts of climate and environmental changes on physical, mental, and emotional health, as observed by Elders and seniors in the Inuit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 50 publications
(41 reference statements)
0
7
0
Order By: Relevance
“…Reports of community engagement varied across studies. Of those studies that reported engaging communities during the design of the research process, they did so to ensure that project goals were in the interest of their partner community, or to enhance the credibility and cultural relevance of the study [55,81,85,89,90,[109][110][111][112]131]. One study in particular reported doing so as part of an Indigenous methodology, which "insist[s] that research topics and questions must reflect community needs, respond to Indigenous goals and protocols, and be collaborative" [52 (p. 463)].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Reports of community engagement varied across studies. Of those studies that reported engaging communities during the design of the research process, they did so to ensure that project goals were in the interest of their partner community, or to enhance the credibility and cultural relevance of the study [55,81,85,89,90,[109][110][111][112]131]. One study in particular reported doing so as part of an Indigenous methodology, which "insist[s] that research topics and questions must reflect community needs, respond to Indigenous goals and protocols, and be collaborative" [52 (p. 463)].…”
Section: Plos Onementioning
confidence: 99%
“…Finally, with regard to dissemination, beyond sharing findings during the analysis phase, the majority of studies reported using a unidirectional approach to sharing the knowledge generated from the research, which meant that results were shared from researchers to the community. However, a small number of studies reported undertaking dissemination activities by working with the community [60,92,108,112,129]. For example, a digital storytelling project by Cunsolo et al resulted in the Rigolet Inuit Community Government establishing the "'My Word': Storytelling and Digital Media Lab, creating the first northern Canadian centre for digital media and community-engaged research and capacity development-Inuit research and facilitation by and for Inuit" [108 (p. 133)].…”
Section: Plos Onementioning
confidence: 99%
“…63,[89][90][91] Constraints to land-based practices have been linked to familial and community tensions and an increase of risk behaviors such as substance use. [92][93][94][95] In reaction to the unfolding decline of species, Inuit community members have also reported sadness and a sense of loss, which Cunsolo et al have described as expressions of ecological grief. 96 These impacts, nested in Inuit culture and Arctic ecosystems, not only involve sadness, anxiety, and interpersonal tensions, but also concerns for future generations and grief.…”
Section: Pathways From Food Security To Mental Healthmentioning
confidence: 99%
“…Adaptation strategies to maintain harvesting, hunting, and fishing practices in context of environmental changes include organizing flights to collect berries when nearby berries are no longer available, replacing snowmobiles lost due to weather events or fragile sea ice, and greater use of boats for transportation. 93,101 These strategies, however, require financial resources. Similarly, maintaining access to healthy market foods in the context of increasing food prices requires purchasing power.…”
Section: Pathways From Food Security To Mental Healthmentioning
confidence: 99%
“…healing or ceremony or it could be anything involving traditional knowledge. Someone in their thirties could be considered an Elder if they have great knowledge of the traditional language, for instance [36]), traditional values, and adaptation practices were mentioned. A Prisma flow chart was constructed for screening, eligibility, and identification of the resources (figure 3).…”
Section: Screening and Eligibilitymentioning
confidence: 99%